Transition-metal-free approach to quinolines via direct oxidative cyclocondensation reaction of N,N-dimethyl enaminones with o-aminobenzyl alcohols - Rao, Kairui; Chai, Zhangmengjie; Zhou, Pan; Liu, Donghan; Sun, Yulin; Yu, Fuchao (Frontiers in Chemistry, 2022)
A transition-metal-free method for the construction of 3-substituted or 3,4-disubstituted quinolines from readily available N,N-dimethyl enaminones and o-aminobenzyl alcohols is reported. The direct oxidative cyclocondensation reaction tolerates broad functional groups, allowing the efficient synthesis of various quinolines in moderate to excellent yields. The reaction involves a C(sp3)-O bond cleavage and a C=N bind and a C=C bond formations during the oxidative cyclization process and the mechanism was proposed.